Preoperative predictors of thrombosis in children with congenital heart disease - V. A. Lastovka; R. F. Tepaev; O. B. Gordeeva; A. R. Bidzhiev; A. A. Chotchaeva (Лечащий Врач)
Thrombosis worsens the course of the disease and increases mortality in children operated on for congenital heart defects. The literature describes in detail the disturbances in the hemostasis system observed after cardiac surgeries performed in conditions of artificial circulation, but there are no indicators that could predict the risk of thrombosis in children. The use of parameters of plasma hemostasis as predictors of thrombosis in the algorithm for diagnosing hemocoagulation disorders in children of the first year of life undergoing surgery for congenital heart defects has been substantiated. This study included 130 children aged 3 days to 11 months 29 days (median age – 5 months), who underwent surgery for congenital heart defects (CHD) using artificial circulation. The patients had thrombosis of various localization: in the vessels of the brain, intracardiac, ischemia of the extremities, etc. The incidence of postoperative thrombosis was 26.9%. All patients were divided into two groups: the first group included children without thrombotic complications (n = 95); in the second – with episodes of thrombosis (n = 35). It was found that the values of von Willebrand factor, plasminogen and D-dimer in the second group significantly exceeded their values in the group of children without thrombosis (p > 0.05). The prognostic significance of these indicators was revealed. Based on the results of the study of this cohort of patients, the concentration of D-dimer, von Willebrand factor activity and plasminogen activity in plasma can be considered as predictors of thrombosis in children with CHD.